Five Constituents in Psoralea corylifolia L. Attenuate Palmitic Acid-Induced Hepatocyte Injury via Inhibiting the Protein Kinase C-α/Nicotinamide-Adenine Dinucleotide Phosphate Oxidase Pathway - Zhou, Lishan; Tang, Jianqiao; Yang, Xuan; Dong, Hui; Xiong, Xiaoli; Huang, Juan; Zhang, Linli; Qin, Huan; Yan, Suqi (Frontiers in Pharmacology, 2020)
Psoralea corylifolia L. (PC) is a traditional Chinese herb used to treat yang deficiency of the spleen and kidney in pediatric disease. Our previous studies have found that PC can alleviate the liver oxidative stress of juvenile mice with nonalcoholic steatohepatitis (NASH), and its mechanism is related to the inhibition of the protein kinase C-α (PKC-α)/nicotinamide-adenine dinucleotide phosphate oxidase (NOX) signaling pathway. The aim of this study was to confirm the aforementioned drug target in vitro and to conduct preliminary screening for some effective compounds of PC on the treatment of NASH. A primary hepatocyte model of non-alcoholic fatty liver disease (NAFLD) was established by palmitic acid (PA). The existence of Psoralen, Isopsoralen, Neobavaisoflavone, Isobavachalcone and Bakuchiol were identified by ultra-performance liquid chromatography. Then, 5 PC compounds were administered. Intracellular triglyceride and total cholesterol content, the cell supernatant alanine aminotransferase and aspartate aminotransferase, and hepatocellular superoxide anion were examined. The changes of PKC-α/NOX signaling pathways in hepatocytes were also determined. Furthermore, PKC-α activator PMA was administered for 4 h before Psoralen intervention was conducted again to detect the changes of PKC-α/NOX signaling pathways. Our data demonstrated that Psoralen, Isopsoralen, and Isobavachalcone decreased intracellular content of triglyceride while all 5 PC compounds improved hepatocellular total cholesterol accumulation and hepatocyte damage in PA-induced primary hepatocyte model of NAFLD. All 5 PC compounds could also reduce hepatocytic superoxide anion levels, NADP/NADPH ratio, NOX activity as well as p47phox protein expression and PKCα activation in hepatocytes. Psoralen exhibited the best efficacy but the effectiveness was lost when pre-stimulated by PMA. The results suggest that Psoralen, Isopsoralen, and Isobavachalcone could improve hepatocyte steatosis; 5 PC compounds could ameliorate hepatocyte injury, relieve oxidative stress, and downregulate the PKC-α/NOX signaling pathway of hepatocytes. In addition, Psoralen exhibits the best efficacy and a prospective PKC-α inhibitor pharmaceutical activity.